Water Quality Assessment Of Dug Well Water And Its Adjoining Buriganga River Reach In The Old Dhaka Of Bangladesh - Barua, Shovon; Islam, M Saiful (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Thirty six dug well water samples from different houses along three transects and four Buriganga river water samples from four different Ghats (boat terminals) of the Old Dhaka of Bangladesh were collected during dry and wet periods for water quality assessment. The depth of these dug wells varies from 3.4 to 16 m with an average depth of 10 m with diurnal variations. The hydrochemical classification shows that the dug well and Buriganga river water samples are Ca-HC03 type. More than 50% dug well water samples were contaminated as concentration levels of Ca, K and Fe in both periods were high whereas over 25% Buriganga river water samples were tainted as concentration levels of Ca, Mg, Fe and Mn in dry season exceeded the drinking water quality standard limits of World Health Organization (WHO), Department of Environment (DOE) and United States Environmental Protection Agency (USEPA). If the dug well water is protected from contamination, the shallow groundwater in this part of Dhaka city should be an alternative perennial source of water especially during the dry season when water scarcity looms large Asiat. Soc. Bangladesh, Sci. 40(2): 207-218, December 2014